Contextualism as an Important Facet of Individualism-Collectivism: Personhood Beliefs Across 37 National Groups. (January 2013) - Owe, Ellinor; Vignoles, Vivian L.; Becker, Maja; Brown, Rupert; Smith, Peter B.; Lee, Spike W. S.; Easterbrook, Matt; Gadre, Tanuja; Zhang, Xiao; Gheorghiu, Mirona; Baguma, Peter; Tatarko, Alexander; et al.
Beliefs about personhood are understood to be a defining feature of individualism-collectivism (I-C), but they have been insufficiently explored, given the emphasis of research on values and self-construals. We propose the construct of contextualism, referring to beliefs about the importance of context in understanding people, as a facet of cultural collectivism. A brief measure was developed and refined across 19 nations (Study 1: N = 5, 241), showing good psychometric properties for cross-cultural use and correlating well at the nation level with other supposed facets and indicators of I-C. In Study 2 ( N = 8, 652), nation-level contextualism predicted ingroup favoritism, corruption, and differential trust of ingroup and outgroup members, while controlling for other facets of I-C, across 35 nations. We conclude that contextualism is an important part of cultural collectivism. This highlights the importance of beliefs alongside values and self-representations and contributes to a wider understanding of cultural processes.